DINAMIKA PERKEMBANGAN PENDIDIKAN ISLAM PADA ABAD KEDUA HIJRIYAH - Hartoyo, Hartoyo; Habibi, Rohim (Al Fattah Ejournal Sma Al Muhammad Cepu, 2023)
The development of science, especially in Islamic education, began in the second century Hijriyah, with various reforms such as the establishment of several mosques, the emergence of Islamic reformers and others, etc. This article discusses how the influence of the golden age of Bani Abbasiyah on learning and education, this research uses a descriptive qualitative approach with data obtained from library research. The results of this research are as follows: The history of Islamic education in the second century AH shows that this period was a golden age for intellectual development and education in the Islamic world. Mosques and madrasas became the main centers of learning, where leading scholars played an important role in shaping educational traditions and encouraging progress in various fields of science. Their contributions not only enriched the Islamic intellectual tradition but also had a far-reaching impact on the exchange of knowledge at the global level, leaving a lasting legacy in the history of education. In addition, the development of curriculum and teaching methods during this period, which emphasized the study of the Qur'an, Hadith, as well as the integration of other sciences such as science, mathematics, and philosophy, created a holistic approach to education. This approach not only strengthened individual faith and morality but also encouraged a sense of community and social responsibility among students. The use of oral traditions in education also helps shape discipline and dedication to studies, thus preparing individuals to play a role in a harmonious and diverse society.